Lord Kubrat and his five sons. Theophanes’ view of the Bulgarians’ arrival in the Balkan Peninsula - Marinow, Kirił (Balcanica Posnaniensia. Acta et studia, 2017)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The Bulgarians’ settlement in the Lower Danube area constituted one of the most significant events in the history of the Balkan Peninsula in the Middle Ages. The Danube Bulgaria’s rise and its territorial expansion changed the political situation in this area. The Bulgarians became Byzantium’s chief opponents in the struggle for establishing ascendancy over the Balkan Peninsula. The analysis of Theophanes’ Chronography, which remains, in addition to the account by Patriarch Nikephoros, the main source of information about these events supports the conclusion that this Byzantine author took a very negative view of the effects of the arrival of these nomads in the former Byzantine territories. Although this account has been analysed in detail by a number of scholars, these authors have paid no attention to the key role of the tale of Khan Kubrat and the disobedience of his five sons who failed to remain faithful to his last wish. The significance of the personal experiences of Theophanes, who witnessed the Bulgarian expansion during the era of Khan Krum, is also omitted from today’s discussion of these issues. These experiences contributed to the way in which he viewed the migration of the ancestors of the distinguished Bulgarian ruler. The chronicler may thus be considered to have offered a very clear view of what the readers should think of the Bulgarians’ arrival in the Balkan territories.